Button Battery Nose: A Case Report - Soumick Ranjan Sahoo (RGUHS Journal of Medical Sciences)
Button batteries are the most hazardous foreign bodies reported in ENT practice. They can cause severe corrosive injury. The nasal cavities are one of the areas where a child accidentally inserts such foreign bodies. A 10-year-old male child was reported to the hospital with purulent rhinorrhea mild nasal bleeding and fever following the accidental insertion of a foreign body in the left nasal passage 1 day back. The foreign body was successfully removed in ENT OPD. It was confirmed as a button battery. It is concluded that such lethal foreign bodies should be urgently removed skillfully and diligently either in emergency or ENT OPD or under general anesthesia in the operation theatre.